T-cell lines producing antigen-specific suppressor factor. - Kontiainen, S; Simpson, E; Bohrer, E; Beverley, P; Herzenberg, L; Fitzpatrick, W; Vogt, P; Torano, A; McKenzie, I; Feldmann, M (1978)
Biochemical characterisation of suppressor factors is hampered by the often minute quantities required to mediate biological effects and by the multiplicity of regulatory pathways involved in immune responses. The authors' knowledge of these factors is derived from functional tests, often combined with serological analysis of the factors. One approach to the analysis of monoclonal cell products is the somatic cell hybridisation technique described by Milstein et al. Using this method, specific antibody-forming cells have been hybridised with myeloma cells, and have yielded clones producing specific antibody. This antibody is particularly useful as it is monoclonal and large quantities can be obtained. Although attempts to produce T-cell hybrids have been successful, the products have not been functional. However, only failures in expression of cytotoxic activity have been described. The authors describe here one antigen-specific suppressor factor (SF)-producing line S1-41 and its products.